Pengaruh Pola Asuh Ibu Dengan Verbal Abuse Terhadap Tumbuh Kembang Anak Usia Pra Sekolah (5-6 Tahun) Di Tk Mujahidin Pontianak - Aspiyanti, Aspiyanti; Haryanto, Haryanto; Putra, Gusti Jhoni (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2016)
Background: According to Terry e. Lawson (1998) psychiatrist of children, violence of children are divided into 4 (four) kinds included, emotional abuse, verbal abuse, physical abuse and sexual abuse. Many children  experienced verbal abuse from their parents that  related to their intelligence, physical appearance, and capabilities. The high violence on the children and less precisely parents in educating them at age 3 to 6 years while its time is the growing of a child where the most prominent influence is the lack of confidence and loss of the child's self image. Objective: To known the influence of mother?s parenting with Verbal Abuse against a Growing of pre School children (5-6 years) at Mujahidin kindergarten Pontianak. Methods: Observational analytic research with cross sectional research design. Results: The percentage of mother?s parenting with the verbal abuse of the largest number of respondents was 72 (72%) have a good parenting and  28 respondents (28%) have not good parenting (verbal abuse) and percentage of growing children with 70 respondents (70%) have a good growth and amount of 30 respondents (30%) have grown less well. Statistical analysis of the test results Influence of mother?s Parenting with Verbal Abuse against a Growing of pre School children (5-6 years) at Mujahidin kindergarten Pontianak used chi square test with a level of significance (Alpha) 0.05 obtained significant results (p = 0.000), which means that the pValue 0.05, then could be inferred that the Ha was accepted which means there was the influence of mother?s Parenting with Verbal Abuse against a Growing of pre School children (5-6 years) at Mujahidin kindergarten Pontianak. Conclusion: Mother?s Parenting with Verbal Abuse has a strong influence on the Growing of pre School children (5-6 years) at Mujahidin kindergarten Pontianak.